1999
DOI: 10.1046/j.1523-5378.1999.98066.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Placebo‐Controlled Trial of Helicobacter pylori Eradication for Iron‐Deficiency Anemia in Preadolescent Children and Adolescents

Abstract: Treatment of H. pylori infection was associated with more rapid response to oral iron therapy as compared with the use of iron therapy alone. Such treatment also led to enhanced iron absorption even in those subjects who did not receive oral iron therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
176
2
9

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(198 citation statements)
references
References 18 publications
9
176
2
9
Order By: Relevance
“…We found that H pylori infection was independently associated with iron deficiency and iron-deficiency anemia among children in this region, with high prevalences of all 3 conditions. This association has been observed in previous studies in rural Alaska 5,6,11 and elsewhere, [16][17][18][19][20][21] but never in a study that was population based, had a relatively large cohort of children, and used a validated measure of active H pylori infection. Our findings suggest that H pylori infection may be an important risk factor for iron deficiency and iron-deficiency anemia among children in rural Alaska and possibly in other areas of the world where these conditions are highly prevalent.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…We found that H pylori infection was independently associated with iron deficiency and iron-deficiency anemia among children in this region, with high prevalences of all 3 conditions. This association has been observed in previous studies in rural Alaska 5,6,11 and elsewhere, [16][17][18][19][20][21] but never in a study that was population based, had a relatively large cohort of children, and used a validated measure of active H pylori infection. Our findings suggest that H pylori infection may be an important risk factor for iron deficiency and iron-deficiency anemia among children in rural Alaska and possibly in other areas of the world where these conditions are highly prevalent.…”
Section: Discussionsupporting
confidence: 70%
“…However, the association was much stronger in children who were 9 years or older (PR: 3.7-4.0) and among those with irondeficiency anemia, and our findings are consistent with previous studies that evaluated the relationship between H pylori and iron deficiency in Alaska and in other settings. 5,6,11,[16][17][18][19][20][21] Confounding by unmeasured socioeconomic factors could also have occurred, but there is relatively little variation in socioeconomic status among Alaska Natives from southwestern Alaska, particularly within villages. Finally, our study was conducted in small villages in rural Alaska, which may limit the generalizability of our findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Six open studies have observed improvements in anaemia and Fe status associated with H. pylori eradication (30)(31)(32)(33)(34)(35) . A randomized controlled trial did suggest a role for H. pylori in causing anaemia among adolescents, but only included small numbers of subjects (36) . A larger randomized study evaluating response of anaemia to different forms of Fe supplementation found that the presence of H. pylori had a negative effect on treatment success (37) , but an even larger open label study failed to demonstrate any improvement in Fe-deficiency anaemia attributable to H. pylori eradication (71) .…”
Section: Discussionmentioning
confidence: 99%
“…12 On the other hand, placebo-controlled trials are not needed to test drug regimens because the spontaneous eradication of the infection is unusual. 13 The present study was not designed as a comparative study because this regimen has never been tested in children, and it should be needed to establish the feasibility of this treatment in children. Finally, the health facilities participating in this study are not tertiary centers, which could lead to better treatment results.…”
Section: Discussionmentioning
confidence: 99%